Determination of Optimum Resources for the Blang Kejeren Electrical System Using PSS Sincal Application - Panggabean, Ulil Azmi; Suriadi, Suriadi; Lubis, Rakhmad Syafutra (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2024)
Currently, the Customer Service Unit (ULP) of the Blang Kejeren State Power Company (PLN) uses the system of the Diesel Power Power Centre (PLTD). Sistem ini terdiri dari PLTD yang dimiliki PLN dan PLtD Lewa, serta beberapa PLTMH (Pusat Listrik Tenaga Mikro Hidro). Aim of the study is to assess the technical viability of the 20 kV ULP Blangkejeren system if supplied with the Kutacane GI and parallel with Distributed Generation (DG). This is because there is no distribution network that can connect the Blangkejeren ULP load centre to the Kutacane GI. Using the PSS Sincal Power System Analysis Application, load scenarios for power plants and distribution networks are modeled and simulated. The findings indicate that the 20kV Ulp Blangkjeren system provided by GI Kutacana, PLTMH, PLTM Lawe, and PLTD Rema is the most appropriate scenario. This situation is regarded as optimal, with a network voltage of 21.07 kV on the ULP Blangkejeren Connection Guard Bus.